Design of a VDBA-Based Memristor Emulator and Its Application for Bio-Sensing Through Instrument Amplifier - Pulak Mondal; Subhasish Banerjee; Mourina Ghosh; Ankur Singh; Santosh Kumar (IEEE Open Journal of Nanotechnology, 2025)
This study describes a VDBA (Voltage Differencing Buffered Amplifier)-based memristor emulator and its use in an instrumentation amplifier for biomedical applications. The proposed grounded and floating memristor has been implemented using a single VDBA and grounded MOS-Capacitor. The VDBA used in this article has also been designed and uses eighteen transistors only. The proposed memristor emulator can be operated in both decremental and incremental modes. The suggested emulator's robustness has been verified using a variety of evaluations, including non-ideal inspection, variations of process corner, temperature swings, and non-volatility performance. Using 45 nm CMOS process parameters in the Cadence environment, the layout has been accomplished, and simulations and observations of the theoretical fingerprint characteristics have been made. The incremental and decremental mode of operation for grounded/floating memristor can be easily obtained by modifying the circuit slightly. The shape of the pinched-hysteresis loop is maintained up to 5 MHz. The functionality of the proposed memristor has also been tested by integrating it with the Instrumentation amplifier to amplify weak bio-medical signals.